Formação docente para o atendimento educacional especializado no município de Imperatriz - LOCATELLI, Adriana (2019)
This master's dissertation aims to analyze the process of teacher education for specialized educational care from the perceptions of teachers of the AEE in the city of Imperatriz. The specific objectives were: Characterize the formation of the teachers of the AEE in the municipality of Imperatriz; Know the difficulties and challenges faced by the teachers of AEE in their pedagogical praxis; To identify the contributions of the continuing education of the teachers of AEE for their teaching performance in the municipality of Imperatriz. To this end, the following research problem was defined: What is the perception of teachers of specialized educational care in the municipality of Imperatriz in relation to their training to work with the target audience of Special Education in AEE? The research was developed within the qualitative approach through the following methodological procedures: bibliographic research and field research; data collection conducted through semi-structured interviews with 13 (thirteen) active teachers of the multifunctional resource rooms of the municipality; documentary research in the Inclusion and Diversity Care Sector for the mapping of the courses offered between 2015 and 2017. Among the main works of the theoretical foundation are: Bueno (1993); Jannuzzi (2004); Mantoan (2006, 2010, 2011, 2013, 2015); Mazzotta (1993, 2011). For the composition of historicity, legal provisions and documents with political guidelines were selected, based on their relevance to the general theme of the research. These include:; Federal Constitution of 1988; Salamanca Declaration of 1994; Law nº 9,394/1996; National Policy on Special Education in the Inclusive Education Perspective; National Guidelines for Human Rights Education and Law nº 13.146/2015. It was found that the teachers have training that enable them to practice teaching in the AEE, also have a vision of Special Education based on inclusive bias in the legal sense and in relation to human rights, in response to the hypothesis established for this work. As part of the teacher's own perception regarding their education, it was found that most teachers consider that their education for AEE in the municipality of Imperatriz is sufficient to meet the range of duties established for the work done in SRMs, however, the participants pointed to problems to be overcome such as: training for inclusive education directed at other school staff, especially for teachers in the common room; higher periodicity and duration of continuing education; autonomy and viability for the school itself to also offer continuing education for its teachers; provision of training according to the need and desire of the teachers of the AEE; availability of Type II Room resources that are needed to serve blind students, such as; Braille printer and Braille typewriter; families' participation in specialized educational services; call and permanence of the absent students; articulation between the teachers of the AEE and the common room; expanding the number of Multifunctional Resource Rooms to better serve and distribute students according to the distance from their homes; Braille course offered at intermediate and advanced levels.